The five senses: A philosophy of mingled bodies - Serres, Michel 1930-2019 (London Continuum, 2008)
The Five Senses represents a defining break in his work, in which he leaves behind traditional philosophy to explore the history and culture of science. By examining the deleterious effects of the systematic downgrading of the senses in Western philosophy, Serres traces a topology of human perception. Writing against the Cartesian tradition and in praise of empiricism, he demonstrates repeatedly, and lyrically, the sterility of systems of knowledge divorced from bodily experience.